Laporan Kasus Penyakit Kusta Tipe Multibasilar (MB) on Therapy dengan Penekanan pada Health Seeking Behavior Pasien di Puskesmas Muara Batu - Muhammad Farhan; Fury Maulina (Lembaga Pengembangan Kinerja Dosen, 2026)
Leprosy remains a significant public health problem in various developing countries, including Indonesia. This disease is caused by Mycobacterium leprae, which attacks the skin and peripheral nerves and can cause long-term physical, psychological, and social impacts if not treated early and adequately. Health-seeking behavior in leprosy patients is also influenced by structural factors such as the availability of health facilities, distance, transportation costs, and the quality of communication between health workers and patients. Research in various endemic countries confirms that friendly, accessible primary health care services that provide comprehensive education can improve early detection and therapy adherence. Patient SA, an 11-year-old child diagnosed with multibacillary (MB) leprosy and has been undergoing treatment for four months. The progression of the disease to MB indicates limitations in early symptom recognition and the family's health-seeking behavior, which may be influenced by low perceptions of disease susceptibility and severity, lack of knowledge, and barriers to accessing health services. However, after the diagnosis was confirmed and education provided by health workers, positive behavioral changes occurred, indicated by the patient's adherence to routine therapy as recommended.